Fermentation of enset (Ensete ventricosum) in the Gamo highlands of Ethiopia: Physicochemical and microbial community dynamics. (August 2018) - Andeta, A.F.; Vandeweyer, D.; Woldesenbet, F.; Eshetu, F.; Hailemicael, A.; Woldeyes, F.; Crauwels, S.; Lievens, B.; Ceusters, J.; Vancampenhout, K.; Van Campenhout, L.
Abstract: Enset ( Ensete ventricosum ) provides staple food for 15 million people in Ethiopia after fermentation into kocho. The fermentation process has hardly been investigated and is prone to optimization. The aim of this study was to investigate the physicochemical and microbial dynamics of fermentation practices in the Gamo highlands. These practices show local variation, but two steps were omnipresent: scraping of the pseudostem and fermenting it in a pit or a bamboo basket. Enset plants were fragmented and fermented for two months in order to investigate the physicochemical (temperature, moisture content, pH and titratable acidity) and microbial dynamics (total viable aerobic counts, counts of Enterobacteriaceae, lactic acid bacteria, yeasts and moulds and Clostridium spores counts, and Illumina Miseq sequencing). Samples were taken on days 1, 7, 15, 17, 31 and 60. The pH decreased, whereas the titratable acidity increased during fermentation. Of all counts those of lactic acid bacteria and Clostridium spores increased during fermentation. Leuconostoc mesenteroides initiated the fermentation. Later on, Prevotella paludivivens, Lactobacillus sp. and Bifidobacterium minimum dominated. These three species are potential candidates for the development of a starter culture. Highlights: Microbial dynamics of three enset varieties across different fermentation days were compared. Metagenetic analysis of the microbial community of fermenting enset was performed for the first time. Microbial community compositions differ between varieties and fermentation days. Few sequences detected correspond to food spoilage microorganisms and potential pathogens. pH, moisture contents and titratable acidity differ across fermentation days and between varieties.